The non-orientable spacetime of the eternal black hole - Ovidiu Racorean (Physics Letters B)
We derive the metric of the BTZ black hole for the special case of interchanging the characteristics of space and time coordinates. We maximally extend the geometry of this interior solution and show that the line element is similar to its exterior solution counterpart. Thus, we assign the thermofield double state dual to this interior geometric construction. As a result, we have two independent thermofield double states corresponding to the BTZ metric: one dual to the exterior solution and one dual to the interior solution. In this scenario, considering both thermofield double states as dual to the full BTZ black hole, we evaluate the partition function of the bulk. The partition function represents a non-orientable spacetime. Additionally, we derive a thermofield double-like state that connects in the gravity dual the regions of spacetime with opposite orientations of space and time. We conclude by discussing the connections between the partition function of the full BTZ black hole and topological invariants that characterize many-body topological phases of matter protected by orientation-reversing symmetries.